The structure of permaculture landscapes in the Philippines - JABEZ JOSHUA M. FLORES; Inocencio Buot. Jr. (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Flores JJM, Buot Jr. IE. 2021. The structure of permaculture landscapes in the Philippines. Biodiversitas 22: 2032-2044. Biodiversity plays a crucial role in sustainable agriculture. Permaculture is a design philosophy that values this role as it consciously integrates diverse components into the farm landscape. The purpose of the study was to characterize the general structure of permaculture landscapes in the Philippines and identify the landscape components that comprise its farming systems. The research was conducted in 12 permaculture farms in 11 provinces in the Philippines in 2018. Aerial photography and farm inventory were employed for data collection. A crop diversity survey was conducted using a modified belt transect method with alternating 20 m2 plots within a 1 ha sampling area. Full enumeration of plant species in each plot was performed to determine species richness and samples were manually counted to compute for the Shannon-Wiener Diversity Index. Results of the study showed that permaculture landscapes were organized into six spatial zones: ‘house,’ ‘garden,’ ‘grazing,’ ‘cash crops,’ ‘food forest,’ and 'wilderness.' It was identified that each zone contained components belonging to six categories: abiotic, biotic, man-made structural, technological, socio-economic, and cultural. 'Biotic' results showed that all sites recorded high species richness (>20-65) with the highest found in Glinoga Organic Farm with 65. Aloha House in Palawan had the highest diversity with a score of 0.311. An analysis of the ratio of plant species per plant category showed that the vegetable/cereal crops dominated the landscape in 50% of sites. While 20% were characterized by tree/fruit-bearing crops. Perennial species were the most abundant in all sites with 75-95% of the total plant species. In conclusion, permaculture provided a design framework for restructuring our agricultural landscapes into diverse and productive ecosystems for human settlement and food production.